Genome-wide comparative analysis of metacaspases in unicellular and filamentous cyanobacteria - Jiang, Qiao (BioMed Central, 2010)
BACKGROUND: Cyanobacteria are an ancient group of photoautotrophic prokaryotes with wide variations in genome size and ecological habitat. Metacaspases (MCAs) are cysteine proteinases that have sequence homology to caspases and play essential roles in programmed cell death (PCD). MCAs have been identified in several prokaryotes, fungi and plants; however, knowledge about cyanobacterial metacaspases still remains obscure. With the availability of sequenced genomes of 33 cyanobacteria, we perform a comparative analysis of metacaspases and explore their distribution, domain structure and evolution. RESULTS: A total of 58 putative MCAs were identified, which are abundant in filamentous diazotrophic cyanobacteria and Acaryochloris marina MBIC 11017 and absent in all Prochlorococcus and marine Synechococcus strains, except Synechococcus sp. PCC 7002. The Cys-His dyad of caspase superfamily is conserved, while mutations (Tyr in place of His and Ser/Asn/Gln/Gly instead of Cys) are also detected in some cyanobacteria. MCAs can be classified into two major families (α and β) based on the additional domain structure. Ten types and a total of 276 additional domains were identified, most of which involves in signal transduction. Apoptotic related NACHT domain was also found in two cyanobacterial MCAs. Phylogenetic tree of MCA catalytic P20 domains coincides well with the domain structure and the phylogenies based on 16s rRNA. CONCLUSIONS: The existence and quantity of MCA genes in unicellular and filamentous cyanobacteria are a function of the genome size and ecological habitat. MCAs of family α and β seem to evolve separately and the recruitment of WD40 additional domain occurs later than the divergence of the two families. In this study, a general framework of sequence-structure-function connections for the metacaspases has been revealed, which may provide new targets for function investigation.